2013
DOI: 10.1007/s11096-013-9889-2
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a community pharmacy service to support adherence and self-management in chronic heart failure

Abstract: Both patients receiving and pharmacists delivering a cognitive HF service felt that it addressed a shortfall in current care. There may be a clearly defined role for pharmacists in supporting patients to address the burden of understanding and managing their condition and treatment, leading to better self management and medicines adherence. This study may inform the development of strategies or policies to improve the process of care for patients with HF and has implications for the development of other extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…28,29,36 However, those using pharmacy services are much less likely to raise concerns of privacy. 37 It seems possible that the general public who are not accessing clinical services through pharmacies may be unaware of recent contractual developments such as the requirement for pharmacies to have consultation rooms.…”
Section: Discussionmentioning
confidence: 99%
“…28,29,36 However, those using pharmacy services are much less likely to raise concerns of privacy. 37 It seems possible that the general public who are not accessing clinical services through pharmacies may be unaware of recent contractual developments such as the requirement for pharmacies to have consultation rooms.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Patient disability, disease burden and decompensation undermine adherence to recommended self-management behaviours. 7,8 Non-adherence to recommended treatment plans is common in CHF, 6,9 with reports that up to 60 % of patients do not adhere to their medication regimens as prescribed and up to 80 % do not adhere to lifestyle recommendations. 5,10 Van der Waal et al 6 also found that patients tend to tolerate exacerbations in their CHF symptoms and delay seeking assistance.…”
Section: Self-management Interventions In Chf: Do They Work?mentioning
confidence: 99%
“…The views and perspectives of patients with LTCs are usually incorporated in research that focus on interventions such as specific services [30, 38], LTCs-specific intervention [39, 40], medicines management services [41, 42] adherence-improving interventions [43], and lifestyle and public health interventions [44, 45]. However, these focus on patients’ preferences, experiences and satisfaction with these services and interventions.…”
Section: Introductionmentioning
confidence: 99%